Bimbingan Teknis Peningkatan Status Desa Tertinggal menjadi Desa Berkembang di Kecamatan Tinanggea Provinsi Sulawesi Tenggara - Tajuddin, Tajuddin; La Ode Anto; Arifuddin, Arifuddin; Ernawati, Ernawati; Wa Ode Rachmasari Ariani (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
The 2024 village development program is titled Technical Guidance for Improving the Status of Disadvantaged Villages to Become Developing Villages in Matandahi Village, Tinanggea District, South Konawe Regency. This activity aims to increase the understanding of village officials about the Building Village Index (IDM). This activity involves village heads, village secretaries, hamlet heads, and chairmen of the Village Consultative Body (BPD), with a focus on increasing their capacity in managing village development. The counseling methods used included lectures and discussions, which were considered effective by 94.44% of participants. The results of the evaluation showed that the majority of participants, 100%, assessed that the village head was ready or very ready to implement the IDM concept. The program also successfully involved balanced participation between age groups and genders, with most participants having an undergraduate educational background. However, there are recommendations to expand the participation of the younger generation and improve the clarity of the material for participants with lower levels of education. In conclusion, this program has a positive impact on village readiness in implementing IDM, with great potential to encourage the acceleration of sustainable village development.